Peran Mediasi Sikap Berwirausaha Pada Pengaruh Pendidikan Kewirausahaan Dan Dukungan Keluarga Terhadap Niat Berwirausaha - Kadek Ema Yulistia; Agoes Ganesha Rahyuda (RELASI : JURNAL EKONOMI, 2023)
This study aims to analyze the mediating role of entrepreneurial attitudes on the effect of entrepreneurship education and family support on the entrepreneurial intentions of students in the Faculty of Economics and Business, Udayana University.The population in this study were students of the Faculty of Economics and Business, Udayana University, batch 2018. The number of samples used in this study was 240 respondents using proportionate random sampling. The research instrument in this study was a questionnaire. The data analysis technique used Partial least square (PLS). The results showed that entrepreneurship education had a positive effect on entrepreneurial intentions. Family support has a positive effect on entrepreneurial intentions. Entrepreneurship education has a positive effect on entrepreneurial attitudes. Family support has a positive effect on entrepreneurial intentions. Entrepreneurial attitudes have a positive effect on entrepreneurial intentions. Entrepreneurial attitude is able to significantly mediate the effect of entrepreneurship education on entrepreneurial intentions. Entrepreneurial attitude is able to significantly mediate the effect of family support on entrepreneurial intentions.